Population dynamics of Cobia Rachycentron canadum (Linnaeus, 1766) off Cochin coast, south-eastern Arabian Sea - Ganga, U.; Pillai, N.G.K; Akhilesh, K.V; Shanis, C.P Rajool; Beni, N; Manjebrayakath, Hashim; Prakasan, D. (Indian Journal of Fisheries, 2012)
Estimated landings of cobia from the Indian EEZ by the commercial fishing vessels are mostly as bycatch in hooks and line cum gillnet and trawl nets. However, the catches are substantial compared to that reported in several other countries of Asia. The species is also gaining considerable importance as a favoured candidate species for sea farming using cages. Very little is known about the fishery and biological characters such as maturation, fecundity and feeding preferences of cobia in Indian seas. Study indicated a fast growth rate with estimates of Lâˆž = 184 cm (FL) and K = 2.6 (yr-1) in cobia. The total mortality rate (Z) was estimated as 5.18, natural mortality (M) was 2.01 and fishing mortality (F) was 3.17 with an exploitation rate (E) of 0.61. The length at first capture (Lc50) estimated from the catch curve was 72 cm. Fecundity was found to be high and variable, with mean fecundity estimated as 12,37,545 eggs with a coefficient of variation (CV) of 16.7. As inferred from the oocyte development pattern, spawning activity is brief and fish is classified as synchronous ovulatory type. The growth parameters and condition factor estimated in this study indicate that relatively high growth rates are also possible in wild stocks considering that food is abundant and the environmental temperature is in the optimum range. Feeding preferences indicated balistid fish and shrimps with a wide variety of food items including finfishes, crustaceans and molluscs present.